PENGARUH KUALITAS PRODUK, KUALITASiPELAYANAN DAN HARGA TERHADAP LOYALITAS PELANGGAN PADA MIE GACOAN CABANG JEMBER - Farida Umi Choiriyah; Khittah Ashilah; Wahyu Frastiyo (LAN TABUR: Jurnal Ekonomi Syariah The Islamic University of KH. Achmad Muzakki Syah Jember, East Java. Jember Jln. Manggar Gebang Poreng 139A Patrang Jember Jawa Timur, 2025)
Mie Gacoan is the first food outlet in Indonesia to serve a noodle menu with a spicylevel that can be adjusted. One of its branches is in the city of Jember which has received apositive response from the community, where since the grand opening until now it is alwayscrowded with customers. The purpose of this study is to test and analyze partially andsimultaneously the effect of product quality, service quality and price on customer loyalty.The method used is descriptive quantitative, with ex post facto research type. The populationin this study is an unlimited number of Mie Gacoan Jember customers and a sample of 150loyal respondents, namely with the criteria of having bought Mie Gacoan products more thantwice. The data collection techniques used are observation and questionnaires. The dataobtained were then analyzed using multiple linear regression techniques. The results of thisstudy show that partially product quality has a positive and significant effect on customerloyalty, service quality has no effect on customer loyalty and price has a positive andsignificant effect on customer loyalty. The test simultaneously obtained the results of productquality, service quality and price simultaneously had a positive and significant effect oncustomer loyalty with a contribution of 37%.Keywords: product quality, service quality, price, customer loyalty